Bamboo The Plant and its Uses - Liese, Walter; Köhl, Michael (Tropical Forestry, 2015)
This book presents the state-of-the-art knowledge on bamboo.  It starts with an introduction to the plant's biology, its taxonomy, habitat, morphology and growth. The cultivation of bamboo is discussed in terms of silviculture, pests and diseases, and harvesting techniques. The book is completed by a comprehensive presentation of the properties of bamboo, its utilization and its preservation. Bamboo is the fastest-growing and most versatile plant on Earth. For centuries it has played an indispensible part in the daily life of millions of people in tropical countries. In recent decades it has gained increasing importance as a substitute for timber. The book was developed as a reference text for scientists, professionals, and graduate students with a strong interest in this unique plant.